2019
DOI: 10.3390/cells8040366
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of ZFAS1 lncRNA in Head and Neck Squamous Cell Carcinomas

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous disease with high mortality. The identification of specific HNSCC biomarkers will increase treatment efficacy and limit the toxicity of current therapeutic strategies. Long non-coding RNAs (lncRNAs) are promising biomarkers. Accordingly, here we investigate the biological role of ZFAS1 and its potential as a biomarker in HNSCC. Methods: The expression level of ZFAS1 in HNSCC cell lines was analyzed using qRT-PCR. Based on the HNSCC TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…As expected, our data revelated that lncRNA ZFAS1 was overexpressed in lung tissues of BLM-induced PF, and overexpression of lncRNA ZFAS1 accelerated the progression of PF through sponging miR-150-5p to upregulate SLC38A1 expression. In addition, previous studies confirmed that lncRNA ZFAS1 acts as an oncogene gene to promote the growth and metastasis of multiple solid tumors by mediating the EMT and proliferation of cancer cells [30,41].…”
Section: Agingmentioning
confidence: 80%
“…As expected, our data revelated that lncRNA ZFAS1 was overexpressed in lung tissues of BLM-induced PF, and overexpression of lncRNA ZFAS1 accelerated the progression of PF through sponging miR-150-5p to upregulate SLC38A1 expression. In addition, previous studies confirmed that lncRNA ZFAS1 acts as an oncogene gene to promote the growth and metastasis of multiple solid tumors by mediating the EMT and proliferation of cancer cells [30,41].…”
Section: Agingmentioning
confidence: 80%
“…Shen et al (2018) reported that higher expression of AC026166.2-001 suppressed cell proliferation and migration in LSCC cells, inhibited cells cycle, and supported cell apoptosis in laryngeal cancer. Also other lncRNAs are upregulated in HNSCC and may display oncogenic properties, such as ZFAS1 (Kolenda et al 2019), PVT1 (Yu et al 2018), CASC9 (Sassenberg et al 2019), TUG1 (Zhang et al 2018b), MIAT (Zhong et al 2019), SNHG20 (Wu et al 2019), or RGMB-AS (Xu and Xi 2019), or downregulated and may act as tumor suppressor genes, such as STR5-AS (Wang et al 2019a), C5orf66-AS1 (Lu et al 2018), AC012456.4 (Hu et al 2018b), LINC01133 (Kong et al 2018), ZNF667, and ZNF667-AS1 (Meng et al 2019).…”
Section: Tumor Suppressor Mirnasmentioning
confidence: 99%
“…Thus, they could assist in identifying various pathologies such as cancer. Additionally, they could also potentially provide information on prognosis or responsiveness to chemo- and radiotherapy [ 12 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%